Avaliação de um programa de formação sobre recursos de alta tecnologia assistiva e escolarização - Lourenço, Gerusa Ferreira (2012)
The right to an appropriate education for students with cerebral palsy requires the provision of resources that will help individuals to improve their performance in everyday tasks more efficiently and independently. The term assistive technology is a term used to refer to a broad range of devices and services, helping individuals achieve greater success in their activities, by improving their functional capabilities. In the case of students with cerebral palsy, assistive technology, which includes devices that involve advanced electronic and computer-based technology, can ensure learners have full access to the curriculum. However, implementation of such a system is a complex process, because it includes students of varying learning abilities; apparatus; task to be performed; and the environment; and moreover, an essential element of its successful implementation is the involvement of a skilled and experienced team of professionals. The aim of the study was to develop and implement a specific assistive technology training program to facilitate the learning process for students with cerebral palsy, and evaluate their effects. The collaborative research project encompassed the development of a training program and its subsequent implementation with a team of professionals in a special school in a town located within the state of São Paulo; and then this program was further evaluated. The participants were nine special education teachers and five professionals of the interdisciplinary team (physiotherapists, speech therapists and psychologist). Nine students with cerebral palsy also participated. The data were collected through focus groups, field notes, open questions on the questionnaires, and videotaping. The results show that the program was effective in promoting positive training for using these resources, and furthermore, that collaborative working between staff and researcher was of overriding importance. The challenge is to find out how to promote the concept into practical actions in order to meet the requirements of established methods. From the results, systematic reviews were carried out and then it was recommended the adoption of a new model for training in this area and to be used within the country, in a didactic format, that enables professionals to be acquainted with their new roles, for successful implementation of assistive technology as tools to access to learning, permanence, and the accomplishments in the development of inclusion process.